PsycEXTRA Dataset 1977
DOI: 10.1037/e525182012-004
|View full text |Cite
|
Sign up to set email alerts
|

Deterring the onset of smoking in children: Knowledge of immediate physiological effects and coping with peer pressure, media pressure, and parent modeling

Abstract: Entering seventh grade, most children believe that smoking endangers their long-term health. Nevertheless, three sources of social pressure were found to often have an overriding influence t o begin smoking: peers, models of smoking parents, and media. Interventions were developed t o train children t o cope with these pressures. Also stressed were immediate rather than long-term physiological effects of smoking. A dependent measure was utilized that generates increased validity of self-reports of smoking. A 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0
2

Year Published

1981
1981
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 5 publications
2
111
0
2
Order By: Relevance
“…Of particular interest in the developed countries, has been the use of methods which address the social influences on smoking. Evans [8] identified peers, parents, and the media as major sources of pressure and in response attempted to familiarize young people with these pressures and with ways of dealing with them. McAlister and others [9,10] developed these ideas further and added the use of peer leaders as educators, activities to increase social commitment not to smoke, and the role-playing of situations that needed resistance to social pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Of particular interest in the developed countries, has been the use of methods which address the social influences on smoking. Evans [8] identified peers, parents, and the media as major sources of pressure and in response attempted to familiarize young people with these pressures and with ways of dealing with them. McAlister and others [9,10] developed these ideas further and added the use of peer leaders as educators, activities to increase social commitment not to smoke, and the role-playing of situations that needed resistance to social pressure.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has, indeed, yielded impressive results in the delay of onset of smoking and drug use in children and adolescents (28)(29)(30)35).…”
Section: Reinforcing Factorsmentioning
confidence: 99%
“…'-6 Five earlier studies have assessed the influence of interventions intended to reduce smoking during pregnancy.7-'°* A substantial body of theory and research suggests that behavior will be influenced if negative consequences of the behavior are: 1) displayed rather than presented in the abstract; 2) clearly linked to the person and not only to others; and 3) shown to exist in the present rather than offered as a possibility for the distant future. [11][12][13][14][15][16][17][18][19][20][21][22][23] Given this guidance, we might expect that telling prenatal patients their smoking will cause lung cancer and heart disease would be ineffective because few could be shown that they have those consequences. In contrast, their behavior might be influenced if they see the level of carbon monoxide (CO) in their alveolar air because that is a concrete demonstration of a current and personal consequence of smoking.…”
Section: Introductionmentioning
confidence: 99%